Improvement of the Technical and Tactical Preparation of Wrestlers with the Consideration of an Individual Combat Style - Yrui Tropin; Mykola Latyshev; Volodymyr Saienko; Inna Holovach; Leonid Rybak; Hanna Tolchieva (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
The present research reviews a programme for improving athletes' technical and tactical preparation with a con- sideration of individual combat style. The program has included training models for each style and has considered the characteristics of the current competitive activities of Greco-Roman wrestlers. Thirty qualified Greco-Roman wrestlers of middle-weight categories have participated in the research. Throughout the experiment (a year-long preparation cycle) the indicators of technical and tactical preparedness of the athletes of the experimental group have improved: the efficiency of defence in stand and ground positions has become higher; the reliability and efficiency of attack and defence actions have increased; the wrestlers have begun to perform a greater number of exercises in stand and ground positions, and to perform successful attacks more often; the interval between the attacks has been shortened. During the experiment, the indicators of technical and tactical preparedness of the athletes of the experimental group have increased from 7.3% to 19.7%, while in the control group from 0.4% to 4.9%. It has been determined that all the considered indicators of the experimental group's technical and tac- tical preparedness after the experiment are statistically higher (р<0.05; р<0.01) than the indicators of the control group. This finding indicates the efficiency of the proposed programme of improvement of technical and tactical preparedness for athletes considering individual combat style and a possibility of its implementation into the training process.